Cholesterol reduction and lack of genotoxic or toxic effects in mice after repeated 21-day oral intake of lemongrass (Cymbopogon citratus) essential oil - Costa, Celso A. R. A. [UNESP]; Bidinotto, Lucas T. [UNESP]; Takahira, Regina K. [UNESP]; Salvadori, Daisy Maria Favero [UNESP]; Barbisan, Luis Fernando [UNESP]; Costa, Mirtes [UNESP] (Pergamon-Elsevier B.V. Ltd, 2011)
Cymbopogon citratus (lemongrass) is currently used in traditional folk medicine. Although this species presents widespread use, there are no scientific data on its efficacy or safety after repeated treatments. Therefore, this work investigated the toxicity and genotoxicity of this lemongrass's essential oil (EO) in male Swiss mice. The single LD50 based on a 24 h acute oral toxicity study was found to be around 3500 mg/kg. In a repeated-dose 21-day oral toxicity study, mice were randomly assigned to two control groups, saline- or Tween 80 0.01%-treated groups, or one of the three experimental groups receiving lemongrass EO (1, 10 or 100 mg/kg). No significant changes in gross pathology, body weight, absolute or relative organ weights, histology (brain, heart, kidneys, liver, lungs, stomach, spleen and urinary bladder), urinalysis or clinical biochemistry were observed in EO-treated mice relative to the control groups. Additionally, blood cholesterol was reduced after EO-treatment at the highest dose tested. Similarly, data from the comet assay in peripheral blood cells showed no genotoxic effect from the EO. In conclusion, our findings verified the safety of lemongrass intake at the doses used in folk medicine and indicated the beneficial effect of reducing the blood cholesterol level. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Cymbopogon citratus; Cholesterol; Lemongrass; Essential oil; Genotoxicity; Acute toxicity